Experimental Investigation of Crack Initiation and Propagation in the Unreinforced Masonry Specimen Subjected to Vertical Settlement - Junbo Wang; Weibing Hu; Xinyu Wang; Yaozhe Liang (Advances in Materials Science and Engineering)
To study the cracking process of the wall caused by differential settlement under a uniformly distributed load on the top of the wall, a laboratory model experiment was carried out on large-scale masonry specimens, and the acoustic emission (AE) technique and digital close-range industrial photogrammetry were adopted to monitor the AE signals and displacement characteristics of the masonry specimens during loading in real time. The results show that, in the case of differential settlement with small settlement on both sides and large settlement in the middle, two main cracks appear on the left and right sides of the wall, extending obliquely from bottom to top. During the loading process, damage of the wall is aggravated due to the differential settlement, and both cumulative ringing count and energy count have different periods of steep rise. With the increase in the load and activation of the AE event, the AE event becomes active, and the cumulative ringing count and cumulative energy curve have an obvious turning point, where the slope of the curve is substantially higher than that before the turning point. By using digital close-range industrial photogrammetry, it is observed that the main oblique crack on the left is mainly caused by the difference in the vertical deformation, while the main oblique crack on the right is caused by different displacements and deformation directions of the wall on both sides of the crack.